The Psychodynamics of Work: Action Research in an Academic Setting - Leclerc, Chantal; Maranda, Marie-France (Canadian Journal of Counselling and Psychotherapy, 2007)
This study on the psychodynamics of work was conducted with some 100 undergraduate students registered in 10 university programs. The main purpose was to analyze the students¹ relationship to their work organization in an economic context characterized by competition, job insecurity, and anxiety about the future. A number of collective defence mechanisms were identified. They are mainly reflected in silence, individualism, isolation and endurance.